2020
DOI: 10.1080/21505594.2020.1838741
|View full text |Cite
|
Sign up to set email alerts
|

Aprepitant, an antiemetic agent, interferes with metal ion homeostasis ofCandida aurisand displays potent synergistic interactions with azole drugs

Abstract: With the rapid increase in the frequency of azole-resistant species, combination therapy appears to be a promising tool to augment the antifungal activity of azole drugs against resistant Candida species. Here, we report the effect of aprepitant, an antiemetic agent, on the antifungal activities of azole drugs against the multidrug-resistant Candida auris . Aprepitant reduced the minimum inhibitory concentration (MIC) of itraconazole in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…There is growing evidence of the efficacy and effectivity of combination regimes, using echinocandins with a second or even third drug, such as amphotericin B, flucytosine, voriconazole, or isavuconazole, among others [ 156 , 157 ]. Less frequently, combinations with other drugs such as co-trimoxazole [ 158 ], lopinavir [ 159 ], aprepitant [ 160 ], or suloctidil [ 161 ] have been used. However, many of these results have been obtained in vitro, and need to be further validated in vivo.…”
Section: Treatment Of Invasive C Auris Infectionsmentioning
confidence: 99%
“…There is growing evidence of the efficacy and effectivity of combination regimes, using echinocandins with a second or even third drug, such as amphotericin B, flucytosine, voriconazole, or isavuconazole, among others [ 156 , 157 ]. Less frequently, combinations with other drugs such as co-trimoxazole [ 158 ], lopinavir [ 159 ], aprepitant [ 160 ], or suloctidil [ 161 ] have been used. However, many of these results have been obtained in vitro, and need to be further validated in vivo.…”
Section: Treatment Of Invasive C Auris Infectionsmentioning
confidence: 99%
“…The combination aprepitant/itraconazole is particularly efficient in an in vivo C. elegans model of infection by C. auris . This synergistic relationship could be mediated by interferences with metal ion homoestasis and subsequent impact on ROS production [ 69 ]. The same team also reported that lopinavir, an HIV protease inhibitor, is able to chemosensitize azole drug.…”
Section: Combination Drugsmentioning
confidence: 99%
“…Another case of drug repurposing is aprepitant, an agent helping to prevent nausea and vomiting, and on the other hand to enhance antifungal effects of azoles against C. auris by chemosensitizing [114]. Authors reported interference of aprepitant/itraconazole with metal ion homeostasis, which led to losing reactive oxygen species' detoxification ability [114]. [115,116] Biofilms formed by Candida spp.…”
Section: Combination Therapies and Novel Treatmentsmentioning
confidence: 99%
“…Findings of a similar work indicate synergistic interactions between suloctidil (sulfur-containing aminoalcohol, vasodilator) and Vcz, and between ebselen (a synthetic organoselenium molecule) and anidulafungin [ 113 ]. Another case of drug repurposing is aprepitant, an agent helping to prevent nausea and vomiting, and on the other hand to enhance antifungal effects of azoles against C. auris by chemosensitizing [ 114 ]. Authors reported interference of aprepitant/itraconazole with metal ion homeostasis, which led to losing reactive oxygen species‘ detoxification ability [ 114 ].…”
Section: Combination Therapies and Novel Treatmentsmentioning
confidence: 99%